The influence and explanation of fringing-induced barrier lowering on sub-100 nm MOSFETs with high-k gate dielectrics - 马飞 刘红侠 匡潜玮 樊继斌 (Chinese physics B, 2012)
The fringing-induced barrier lowering（FIBL） effect of sub-100 nm MOSFETs with high-k gate dielectrics is investigated using a two-dimensional device simulator.An equivalent capacitance theory is proposed to explain the physics mechanism of the FIBL effect.The FIBL effect is enhanced and the short channel performance is degraded with increasing capacitance.Based on equivalent capacitance theory,the influences of channel length,junction depth,gate/lightly doped drain（LDD） overlap length,spacer material and spacer width on FIBL is thoroughly investigated.A stack gate dielectric is presented to suppress the FIBL effect.